Effects of chromium propionate supplementation on production performance, blood parameters, ruminal fermentation indices, and microbial diversity in heat-stressed Holstein dairy cows - Zhang, Bihong; Wen, Yongqiang; Zhang, Zixin; Liu, Qimin; Wang, Yazhou; Zhao, Chenxu; Wang, Jianguo (Frontiers in Veterinary Science, 2025)
Global warming increases the risk of heat stress in dairy cattle, thereby jeopardizing their health and the economic benefits of dairy farms. Chromium propionate (CrPro) is a chromium source permitted for use in feed additives. However, research on the effects of CrPro on heat-stressed dairy cows is limited. Therefore, this study assessed the effects of different doses of CrPro on heat-stressed dairy cows. Holstein dairy cows with similar body condition, milk yield, and parity were randomly divided into three groups: the control group (Con), the low-dose group (CrL), and the high-dose group (CrH), with 10 cows per group. CrPro was supplemented at doses of 0, 4, and 8 mg/(d·cow) in the basal diets of each group, respectively. The trial lasted for 45 days. The temperature-humidity index (THI) in the cowshed was monitored daily to assess the heat stress status of the cows. Daily milk yield was recorded, and rectal temperature was measured according to experimental requirements. Milk composition, antioxidant capacity, liver enzyme activity, lipid metabolism, and other parameters were analyzed. The composition and diversity of the rumen microbiota were also assessed. Results showed that the average THI in the cowshed during the trial period (0–45 days) was 74.97 ± 2.85, indicating that dairy cows used in this study experienced mild heat stress. Compared with the Con group, the CrL and CrH groups had reduced rectal temperature and respiratory rate. The CrH group had significantly lower milk yield loss and somatic cell count (p < 0.05). No significant differences were observed in milk composition, antioxidant capacity, liver enzyme activity, or lipid metabolism between the CrL and CrH groups (p > 0.05). Compared with the CrH group, the CrL group had lower volatile fatty acids (VFAs) (acetate, propionate, butyrate, isobutyrate, valerate, and isovalerate) in rumen fluid. Compared with the control group, both CrL and CrH groups exhibited enhanced microbial abundance and an optimized ruminal community structure. Overall, an 8 mg/(d·cow) dose of CrPro had a greater impact on improving production performance and economic benefits. The findings of this study provide data support for selecting an appropriate CrPro dosage to reduce heat stress-induced economic losses on dairy farms.